World Economic Outlook for 2022 and 2023 - Chang Woon Nam (CESifo Forum, 2022)
The war in Ukraine slows the global recovery. This article briefly presents the IMF's growth forecasts for 2022 and 2023. In addition to addressing the immediate challenges of the war and the pandemic, it also highlights the need for continued, focused longer-term economic policies, particularly in the areas of structural, digital, and energy transformation.
Keywords: 330